Reconfigurable patch antenna by RF MEMS switches - Alam, A. H. M. Zahirul; Islam, Md. Rafiqul (2009)
A planar reconfigurable microstrip antenna is proposed by using RF MEMS switches. The proposed antenna structure comprises a center patch antenna known as driven patch and two adjacent microstrip patches defined as wing patches. Cantilever MEMS bridges are introduced to provide to operate antenna either 21.73 GHz or 23.6 GHz depending on the position of the MEMS switches. The design is performed by using 3D electromagnetic simulator HFSS considering ideal MEMS switches.